Can herbal extracts serve as antibacterial root canal irrigating solutions? Antimicrobial efficacy of Tylophora indica, Curcumin longa, Phyllanthus amarus, and sodium hypochlorite on Enterococcus faecalis biofilms formed on tooth substrate: In vitro study - Shan Sainudeen; Veena S Nair; Mohammad Zarbah; Anshad Mohamed Abdulla; Chawre Mustufa Najeeb; Sivadas Ganapathy (Wolters Kluwer Medknow Publications, 2020)
Aim: The purpose of this study was to evaluate the antimicrobial efficacy of Tylophora indica, Curcumin longa, and Phyllanthus amarus on Enterococcus faecalis biofilms formed on the tooth substrate. Sodium hypochlorite was used as a positive control. DMSO (dimethyl sulfoxide), the vehicle for the herbal extracts, was used as the negative control. Materials and Methods: Extracted human teeth were biomechanically prepared, vertically sectioned, placed in the tissue culture wells exposing the root canal surface to E. faecalis to form a biofilm. At the end of the third week, all groups were treated for 15 min with the test solutions and the control. The results were analyzed both quantitatively and qualitatively. Results: Statistical analysis was performed by using one-way analysis of variance and compared by the Mann-Whitney test using the Statistical Package for the Social Sciences (SPSS) software, version 20.0. The qualitative assay with the 3-week biofilm on the canal portion showed complete inhibition of bacterial growth for NaOCl, whereas samples treated with herbal solutions showed significant reduction of bacterial growth compared to control group, which showed 139.9 × 109 CFU/mL among the experimental herbal solutions groups. P. amarus has shown maximum bacterial count followed by C. longa and T. indica. Conclusion: NaOCl 5% showed maximum antibacterial activity against 3-week biofilm on tooth substrate. T. indica, P. amarus, and C. longa showed statistically significant antibacterial activity against 3-week biofilm. The use of herbal alternatives might prove to be advantageous considering the several undesirable characteristics of NaOCl.